Determinants of banks expansion in the East African Community: An empirical analysis of Kenyan banks - Lucas Njoroge; Shem Ouma (Kenya Bankers Association (KBA), 2014)
The study examines the determinants of banks expansion in the East African Community (EAC) using data for Kenyan banks. The study estimates both a probit model based on a binary choice of expanding to the region or not, and a pooled panel regression model based on a bank's actual flow of foreign direct investments in associates, subsidiaries and joint ventures in the region. The results show the importance of factors associated with the need to follow bank clients abroad, efficiency and size of the banks, and the potential market opportunities of the host countries. Larger, profitable and more efficient Kenyan banks have been at a competitive advantage to expand to the region. However, this does not imply that the smaller banks are not expanding to the region, rather, that the expansion of larger banks is more conspicuous. Consistent with other studies, Kenyan banks seem to prefer to expand to a country where inflation is relatively low and less likely to cause macroeconomic instability. The findings support the on-going deeper economic integration in terms of more trade and investment. This suggests that most Kenyan banks are expanding to the region in order to provide their home clients with the services on site and to take advantage of the large potential for business of the regional economies.
Keywords: 330; cross-border banking; Banks expansion; EAC economies; deeper integration